Evaluation of dietary treatment and amino acid supplementation in organic acidurias and urea‐cycle disorders: On the basis of information from a European multicenter registry. Issue 6 (27th February 2019) - Molema, Femke; Gleich, Florian; Burgard, Peter; van der Ploeg, Ans T.; Summar, Marshall L.; Chapman, Kimberly A.; Barić, Ivo; Lund, Allan M.; Kölker, Stefan; Williams, Monique; ,
Abstract : Organic acidurias (OAD) and urea‐cycle disorders (UCD) are rare inherited disorders affecting amino acid and protein metabolism. As dietary practice varies widely, we assessed their long‐term prescribed dietary treatment against published guideline and studied plasma amino acids levels. We analyzed data from the first visit recorded in the European registry and network for intoxication type metabolic diseases (E‐IMD, Chafea no. 2010 12 01). In total, 271 methylmalonic aciduria (MMA) and propionic aciduria (PA) and 361 UCD patients were included. Median natural protein prescription was consistent with the recommended daily allowance (RDA), plasma L‐valine (57%), and L‐isoleucine (55%) levels in MMA and PA lay below reference ranges. Plasma levels were particularly low in patients who received amino acid mixtures (AAMs‐OAD) and L‐isoleucine:L‐leucine:L‐valine (BCAA) ratio was 1.0:3.0:3.2. In UCD patients, plasma L‐valine, L‐isoleucine, and L‐leucine levels lay below reference ranges in 18%, 30%, and 31%, respectively. In symptomatic UCD patients who received AAM‐UCD, the median natural protein prescription lay below RDA, while their L‐valine and L‐isoleucine levels and plasma BCAA ratios were comparable to those in patients who did not receive AAM‐UCD. Notably, in patients with ornithine transcarbamylase syndrome (OTC‐D), carbamylphosphate synthetase 1 syndrome (CPS1‐D) and hyperammonemia‐hyperornithinemia‐homocitrullinemia (HHH) syndrome selective L‐citrulline supplementation resulted in higher plasma L‐arginine levels than selective L‐arginine supplementation. In conclusion, while MMA and PA patients who received AAMs‐OAD had very low BCAA levels and disturbed plasma BCAA ratios, AAMs‐UCD seemed to help UCD patients obtain normal BCAA levels. In patients with OTC‐D, CPS1‐D, and HHH syndrome, selective L‐citrulline seemed preferable to selective L‐arginine supplementation.